State Fragility Case Studies and Comparisons - Bizhan, Nematullah (Routledge Series on Global Order Studies, 2023)
Presenting case studies and comparisons across seven countries, this book addresses key questions as to the nature of state fragility, policies used to mitigate it, assessment of outcomes and prospects. It offers a novel empirical contribution in examining a range of distinct but interdependent dimensions of state fragility, not only focusing on questions of state legitimacy, capacity and authority, but also involving the economy and resilience to political and economic shocks, as well as at vital questions of context and diversity. Examining Afghanistan, Lebanon, Burundi, Pakistan, Sierra Leone, Papua New Guinea and Rwanda within the context of their different local circumstances, and within broader questions of global security, the book identifies unique factors that have played a part in their specific context and explores key drivers and dominant features. This book will be of key interest to scholars and students of state fragility and more broadly to students of politics, public policy, development studies, state-society relations, political economy, state building, peace and conflict studies, international studies, security studies regional studies., as well as NGOs and international organizations.